Machine Translation Research A Scientometric Assessment of Global Publications Output during 2007 16 - Gupta, Brij Mohan; Dhawan, S.M. (DESIDOC Journal of Library & Information Technology, 2019)
The present study provides a quantitative and qualitative description of global machine translation research published during 2007-16 and as indexed in Scopus database. The study profiles research in the field on a series of measures, such as publications growth rate, global share, citation impact, share of international collaborative papers and distribution of publications by sub-areas. The study also profiles top contributing countries, organisations and authors in machine translation research on a series of bibliometric indicators. The study further reports characteristics of highly cited papers in the field.